2018
DOI: 10.1186/s13059-018-1573-3
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyldeoxyadenosine directs nucleosome positioning in Tetrahymena DNA

Abstract: BackgroundN6-methyldeoxyadenosine (6mA or m6dA) was shown more than 40 years ago in simple eukaryotes. Recent studies revealed the presence of 6mA in more prevalent eukaryotes, even in vertebrates. However, functional characterizations have been limited.ResultsWe use Tetrahymena thermophila as a model organism to examine the effects of 6mA on nucleosome positioning. Independent methods reveal the enrichment of 6mA near and after transcription start sites with a periodic pattern and anti-correlation relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 48 publications
2
54
0
Order By: Relevance
“…However, there are species where m 6 A occurs endogenously and is strongly correlated with patterns of accessibility and nucleosome positioning (e.g. Chlamydomonas 45 and Tetrahymena 46,47 ). Alternative methylation strategies such as 4mC methyltransferases 48 , cytidine deaminases 49 , or the conversion of thymine to modified bases such as 5hydroxymethyluracil (dhmU) 50 are areas of potential future exploration.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are species where m 6 A occurs endogenously and is strongly correlated with patterns of accessibility and nucleosome positioning (e.g. Chlamydomonas 45 and Tetrahymena 46,47 ). Alternative methylation strategies such as 4mC methyltransferases 48 , cytidine deaminases 49 , or the conversion of thymine to modified bases such as 5hydroxymethyluracil (dhmU) 50 are areas of potential future exploration.…”
Section: Discussionmentioning
confidence: 99%
“…2e, 3f) (Wang et al 2017a). By in vitro nucleosome assembly in Tetrahymena, a recent study revealed that the distribution pattern of nucleosomes could be recapitulated in native genomic DNA but not in DNA without 6mA (Luo et al 2018). A study of another ciliate, Oxytricha trifallax, demonstrated that nucleosome fuzziness increased after loss of 6mA in the linker DNA (Beh et al 2019).…”
Section: Epigenetic Regulation Of Nucleosome Distributionmentioning
confidence: 99%
“…Further analysis revealed that 6mA accumulated in linker DNA regions between well-positioned nucleosomes (Fig. 2d, g), but the direction of the causal effect remains to be determined (Luo et al 2018). Moreover, nucleosomes adjacent to 6mA were enriched with the conserved histone variant H2A.Z ( Fig.…”
Section: Introductionmentioning
confidence: 95%
“…Data from Tetrahymena shows that 6 mA is only present in the transcriptionally active MAC and is preferentially enriched in the consensus sequence 5′-AT-3′ [ 133 , 134 ]. 6 mA modifications also localize to linker DNA regions downstream of the transcription start site (TSS of Polymerase II transcribed genes) and directly influence nucleosome positioning [ 133 , 136 138 ]. Tetrahymena ’s MT-A70 homologue ATM1 (6mA DNA methyltransferase) is required for the normal growth and development of the cell following sex [ 139 ].…”
Section: Developmentally Regulated Genome Rearrangementsmentioning
confidence: 99%